MOTIF PENGGUNAAN AKUN INSTAGRAM @JONAN_55 DAN KEPUASAN FOLLOWERS DALAM MENDAPATKAN HIBURAN - Novriani, Venny; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Instagram is a social media which is now a multifunctional media, for example as a medium for entertainment, business, culinary, travel and so forth. The diversity of functions of Instagram is a way for audiences to satisfy their needs, so that media users use Instagram with different goals, one of which is the need for entertainment. This study aims to determine the level of motives for using the Instagram account @ jonan_55 and the level of satisfaction obtained by followers in getting entertainment and measuring the gap of satisfaction (Gratification Discrepancy) between the motives for using an Instagram account @ jonan_55 (GS) and the satisfaction received in getting entertainment (GO) .This research uses a quantitative method with a descriptive approach. The theory used in this research is Use and Gratification which sees the audience using mass media based on certain motives. The sample in this study amounted to 400 respondents and the technique of determining the sample using random sampling. The data analysis technique in this study uses a gap analysis (discrepancy) between motives and entertainment satisfaction on the Instagram account @ jonan_55. The data obtained is the result of processing SPSS 21.The results of this study based on the gap analysis showed that out of the 10 needs items offered to respondents, all were able to be fulfilled by the Instagram account @ jonan_55, but dominated by 6 items in the low category and one item in the high category, and only 3 item needs were in the medium category. And a comparative analysis of the total mean Gratification Sought (GS) value of 31.040 is smaller than the total mean Gratification Obtained (GO) value of 29,940 with a difference of 1.1 means the mean GSï€¾mean GO, meaning that there is no large gap between the motives for using the Instagram account @ jonan_55 and satisfaction of followers in getting entertainment. So overall it shows that the Instagram account @ jonan_55 is not maximized in meeting the entertainment needs of its followers.Â Keyword: Motif Penggunaan, Akun Instagram @jonan_55, Kepuasan Hiburan